Utilizing the intelligent sensing function of conjugated materials to create intelligent flute training equipment - Lu, Jialiang (Frontiers in Chemistry, 2023)
The manufacturing of flute has always relied on traditional ceramics and metals, and may be affected by various factors during the manufacturing process, resulting in poor tone quality and performance of the instrument, as well as the lack of intelligent sensing function, resulting in poor performance. The purpose of this article was to explore the use of the intelligent sensing function of conjugated materials to create intelligent flute training equipment, achieve automatic tuning, volume control, etc., and improve the playing experience and training effect of the instrument. This article analyzed the intelligent sensing function of conjugated materials and applied them to intelligent flute training equipment. Some special organic molecules in conjugated materials have the property of photo induced deformation. By introducing photosensitive materials in appropriate positions, the size and shape of the flute's sound hole were changed, thereby adjusting the timbre. Photoelectric sensors based on conjugated materials were used to perceive the performer's playing in real-time, and provide guidance based on the data detected by the sensors. The performer can achieve greater space for timbre change and expressive power. The average delay time of the conjugated material flute was reduced by 73.1% compared to the average delay time of the ceramic flute, and by 63.5% compared to the average delay time of the metal flute. The conjugated material flute is more intelligent and can quickly respond to the player's playing and automatically control and respond. The results of this article emphasized that the intelligent sensing function of conjugated materials could provide more intelligent flute training equipment, help performers improve their performance level, and provide more comprehensive training methods.